1986
DOI: 10.1111/j.1365-2605.1986.tb00894.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of sperm‐associated immunoglobulins in infertile men with suspected autoimmunity to sperm

Abstract: Semen samples from 120 infertile men with suspected autoimmunity to sperm were investigated by a direct immunobead test (IBT). Fifty-three (44%) of them had 10% or more motile sperm coated with anti-IgG and/or anti-IgA immunobeads. Both classes of immunoglobulins were found to be present in 88.7% of the antibody positive ejaculates. These sperm-bound Igs were associated with sperm autoagglutination in 80% of the ejaculates and with decreased sperm penetration into cervical mucus in 97.6% of the cases. The clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

1992
1992
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 5 publications
0
6
0
4
Order By: Relevance
“…Elles sont constitu6es par l'agglutination des spermatozoides, la diminution de la mobilit6 progressive, de la vitalit6 et quelquefois de la num6ration des spermatozo~des [8,25,26,110].…”
Section: Anomalies Du Spermogrammeunclassified
See 2 more Smart Citations
“…Elles sont constitu6es par l'agglutination des spermatozoides, la diminution de la mobilit6 progressive, de la vitalit6 et quelquefois de la num6ration des spermatozo~des [8,25,26,110].…”
Section: Anomalies Du Spermogrammeunclassified
“…Ils reprEsentent l'effet le mieux connu et le plus visible de 1'interfErence des anticorps avec la fertilit6 in vivo ou in vitro [25,29,30,75]. Les tests post-coitaux ou les tests de pEnEtration croisEe sont nEgatifs ou pauvres en presence d'un mucus cervical ovulatoire.…”
Section: B) Les Tests Dans La Glaireunclassified
See 1 more Smart Citation
“…La frEquence d'IBT positifs (plus de 20% de spermatozoides mobiles porteurs de billes) dansles populations d'hommes infertiles non sElectionnEs varie entre 7 et 10% [7,18,20]. Dans une population de 120 hommes infertiles suspects d'auto-immunisation, nous avons trouv6 44% de spermes positifs en IBT [14].…”
Section: Reaction D'agglutination Mixte (Mar Test)unclassified
“…Therefore, minimizing exposure time might be important to prevent immobilization and sperm lysis. Sperm-bound immunoglobulins are associated with sperm autoagglutination in 80 % of the ejaculates and they decreased sperm penetration into cervical mucus in 97.6 % of the cases; furthermore, the proportion of ASA-bound sperm correlates with sperm penetration into cervical mucus [9][10][11]. It has been suggested that the cervical mucus aids in the selection of the most fertile sperm of an ejaculate by acting as an immunological filter, preventing the passage of sperm coated with ASA [12].…”
Section: Introductionmentioning
confidence: 96%